Strengthening Spiritual Practices among Community: Dhikr Activities in Negeri Sembilan, Malaysia - Abdul Hamid, Mohammad Fahmi; Meerangani, Khairul Azhar; Suliaman, Ishak; Md Ariffin, Mohd Farhan; Abdul Halim, Amran (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2021)
Tarekat tasawuf has been established in Negeri Sembilan since 1900 and began to strengthen its existence in spiritual activities such as the implementation of zikr tarekat tasawuf activities among the local community. This article will highlight the impact of implementing the zikr activities tarekat tasawuf, which is implemented periodically on the spiritual strengthening of the community in Negeri Sembilan. A qualitative approach is used involving library studies, review of relevant documents, and interviews with the Registrar of Tarekat, Tasawuf Division of the Negeri Sembilan Mufti Department, and the Syeikh of the tarekat involved. Basically, there are 13 Sufi practice centers around Negeri Sembilan that conduct regular zikr activities that impact the community. The existence of tarekat practice centers in Negeri Sembilan has been plotted to see the distribution and centralization of tarekat centers. In addition, the form of zikr practiced in the zikr ceremony is also explained through a simple framework built. The results also showed that the Seremban district is the highest area with a tarekat practice center. Indirectly, the zikr activities, tarekat tasawuf, have provided space for the local community to engage in more systematic spiritual activities. The efforts implemented by the Sufi tarekat practice center in Negeri Sembilan are expected to be used as an example by other states in Malaysia so that the community is more interested in the Sufi tarekat zikr ceremony.